A pilot study on left ventricular dimensions and wall stress before and after submaximal exercise. Issue 3 (September 1979) - Cahill, N. S.; O'Brien, M.; Rodahl, A.; Allen, J. F.; Knight, D.; Dolphin, C.
Abstract : Left ventricle dimensions and wall stress were measured echocardiographically before and immediately after exercise in 14 athletes and 7 control subjects. Our findings suggest that afterload is an important determinant of cardiac performance and wall hypertrophy in athletes. In spite of major changes in heart rate and blood pressure, left ventricular wall stress remains unchanged following submaximal exercise, in trained and untrained hearts. It would appear that the changes in heart size during exercise are to a large extent limited in untrained ventricles, as smaller left ventricular dimensions are required, to "normalise" wall stress. This results in a lower stroke volume for a given stroke dimensional change. Consequently cardiac output is a function of heart rate rather than stroke volume in untrained subjects. The effect of increased muscle mass in athletes, is to permit larger left ventricular dimensions for a given afterload, thus stroke volume can be augmented. The increase h/R ratio suggests that afterload is more important than preload in the development of left ventricular hypertrophy in rowers and swimmers.